Failed shoulder stabilization procedure in the elderly: reverse shoulder replacement is the treatment ultimum - Narayanan, Subramanian Kanthalu; Muthusamy, Navaladi; Pauldhurai, Vanaj Kumar (International Journal of Research in Orthopaedics, 2019)
Shoulder instability, though often seen in younger individuals it can also occur in the elderly. Shoulder instability in the elderly is often missed and definitive management gets delayed. Treatment delay has a significant influence on the choice of surgical procedure and its functional outcome. We report a 77 year old female who presented with a missed anterior dislocation of the glenohumeral joint. She had undergone an open Latarjet procedure for shoulder instability eight months before her presentation. Considering her age, humeral head bone defects, rotator cuff tear and degenerative changes in the joint we opted for a Reverse Shoulder Replacement in her. The patient now has a pain free, stable and mobile shoulder joint. Her pre-operative Constant score was 11 which improved to 67 at 6 months follow up. Now after 12 months follow up, she has active flexion up to 150°, abduction- 90°, external rotation- 10°, internal rotation- 300 and extension- 50°. Reverse shoulder replacement is a viable treatment option for chronic locked shoulder dislocations with concomitant rotator cuff lesions. Though there is a concern about failure of the glenoid component due to bone defects, RSA is still preferable in elderly patients with low functional demand.